(untitled) (Mongolian Journal of Astronomy and Geophysics, 2024)
Gobi Altay fault is one of the largest intra-continental faults in Asia where was conducted using the seismic exploration survey which is an effective geophysical method for detecting faults. Based on the shallow seismic data from an active seismic survey in surrounded eastern part of Toromkhon valley, Bogd mountain fault zone, Gobi-Alati range, southwestern Mongolia. The main goal of the work was to identify the features of fault zones using seismic instruments to develop a methodology for identifying late Holocene fault zones that are currently eroded. The seismic survey result shows that the combination of shallow seismic migration and 2D velocity inversion model. The seismic data were processed along a straight CMP line and an interpretation was made under the migrated time section and 2D velocity inversion model based on finite element method.